American Foreign Policy Fiascos - Daghrir, Wassim (Advances in Social Sciences Research Journal, 2017)
The US policy toward the Sandinista regime in Nicaragua represented one of the most complex and most controversial chapters in the history of American foreign policy. The tiny Nicaragua, a nation of 2.5 million, retained the complete attention of a superpower 100 times larger. In fact, few foreign policy issues commanded the attention of the foreign policy establishment as much as the Nicaraguan Revolution. For over a decade, US policy makers directed an exceptional amount of human and intellectual energy to design the lines of a complex policy. US efforts to contain the Nicaraguan revolution took the shape of an extended low-intensity conflict based on diplomatic pressure, economic pressure, intelligence operations, and a covert counter-revolutionary war, mixed with a colossal public relations campaign. The US-Nicaraguan relations stimulated severe political debates in Washington, caused one of the most noticeable Executive-Legislative disagreements, and even led to one of the most delicate presidential scandals in the political history of the United States. But why was Washington so worried about the Nicaraguan Revolution? Why did such a tiny country with no vital strategic resources, and with less than one percent of total US foreign investment, warrant so much attention from the American power elite? This article tries to offer some answers to the Nicaraguan issue through a description of the various strategies and instruments of policies used by the Carter, Reagan, and Bush administrations.